A self-healing composite actuator for multifunctional soft robot via photo-welding. (1st June 2021) - Liu, Mingxia; Zhu, Shu; Huang, Yanjia; Lin, Zihui; Liu, Weiping; Yang, Lili; Ge, Dengteng
Abstract: With the structure design and muscle-like actuators, soft robots have been extensively studied for various application potentials in rescue exploration, medical rehabilitation, military reconnaissance etc. It is highly desirable yet challenging to develop fast 3D-assembly, multifunctional and self-healing soft robots to adapt to rapid changing environments. Inspired by multi-bit screwdriver, we address this challenge using a self-healing light-driven shape memory polymer via photo-welding. Semicrystalline poly (ethylene-co-vinyl acetate) (EVA) involved with silver nanowires (AgNWs) exhibit reversible light-trigged morphing behavior in air or underwater. Additionally, the re-crosslinking of EVA molecular and chain mobility under photothermal effect endows the composite with self-healing property, resulting in fast assembly of soft robotics with sophisticated 3D structures via photo-welding. More importantly, to change the function, the unit could be first cleaved from the main body and then another programmed component could be photo-welded on the main body. Our work provides a facile and cost-effective strategy for creating multifunctional, self-healing soft robots.